KESULITAN-KESULITAN KHUSUS DALAM PEMAHAMAN BACAAN BAHASA INGGRIS DI KALANGAN PEMBELAJAR LANJUT INDONESIA (TYPICAL READING COMPREHENSION PROBLEMS AMONG INDONESIAN ADVANCED LEARNERS) - Johan, A. Ghani (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2006)
Every learner or group of learners at a certain stage of learning may have certaindifficulties of their own; so is the case with students undertaking English readingcomprehension. There are reading skills presenting reading difficulties toIndonesian learners. Some of them can be overcome at early stages of theirlearning; some others remain inherent problems throughout their study. Teachersfrequently assume that everything they previously presented to their students hasbeen understood and put into practice by their students. The fact is that it is notalways the case. It often turns out that the learners are still not yet able to apply theknowledge that has been taught or the reading skills that has been developed. Thishappens because of incomplete understanding or lack of practice or due to thecomplexity of the language features being studied. On the basis of the writer'sobservation and experience in teaching reading comprehension and translation,the writer opines that there are some language features and constructions inEnglish which present typical problems even to such Indonesian advancedlearners as students at the English Language Education Department, Faculty ofLanguages and Arts, State University of Yogyakarta, in their fourth to eighthsemesters. Those language features and constructions are, among others, nounphrases, free adjuncts or participial phrases, the formal it, the pronouns that andthose, clues to subject-predicate identification, various word functions andmeanings (included in word identification), signals for reading between the lines,and discourse markers.Keywords: typical reading problems, reading skills